PENTINGNYA MINDFULNESS UNTUK MENGATASI STRES PADA SISWA DI SEKOLAH DENGAN SISTEM BOARDING SCHOOL - Eva Palupi (EDU RESEARCH, 2024)
Stress is a common challenge experienced by students, especially in a boarding school environment with high academic and social pressures. This study aims to examine the importance of mindfulness as an approach to cope with stress in boarding school students. Mindfulness, which refers to full awareness of the present moment without judgment, can help students manage emotions and improve psychological well-being. This study used a literature review approach and collected data from various relevant studies. The results showed that mindfulness practice significantly reduced stress levels by increasing students' ability to deal with pressure more adaptively. In addition, mindfulness was shown to improve concentration, self-control, and more positive social relationships. The implementation of mindfulness in the form of training programs in boarding schools is recommended to support students' mental health. Thus, mindfulness is not only relevant as an intervention to reduce stress, but also as a strategy to build a more supportive learning environment.